A new species of miniaturized toadlet, genus Brachycephalus (Anura: Brachycephalidae), from the atlantic forest of southeastern Brazil - Clemente-Carvalho, Rute B.G.; Giaretta, Ariovaldo A.; Condez, Thais H. [UNESP]; Haddad, Célio F.B. [UNESP]; Dos Reis, Sergio F. (Herpetologists League, 2012)
A new species of miniaturized froglet (genus Brachycephalus) is described from Morro Prumirim in the municipality of Ubatuba, São Paulo, southeastern Brazil. Specimens were collected from the leaf litter at approximately 800 m above sea level. The new species is distinguished from all its congeners by the combination of the following characters: snout-vent length 8.7-13.4 mm; skin on head and dorsum with dermal ossification; general color orange, with a narrow brownish vertebral stripe and belly without spots; and skull, spinal processes of sacral and pre-sacral vertebrae, and process of the fourth vertebra hyperossified. Canonical variates analysis of linear body measurement demonstrates that the new species is easily discriminated from other Brachycephalus species with which it shares an intermediate condition of hyperossification. © 2012 by The Herpetologists League, Inc.
Keywords: Amphibia; Anura; Atlantic rain forest; Brachycephalus; Brazil; New species; canonical analysis; frog; geographical distribution; leaf litter; new species; rainforest; skin; skull; type specimen; zoogeography; Atlantic Forest; Sao Paulo [Brazil]; Ubatuba